Variações anatômicas da Tenossinovite de De Quervain: comparação dos achados cirúrgicos em pacientes portadores da doença com os achados em cadáveres - Paulo Randal Pires Junior (2014)
Objective: Evaluate anatomic variations in the first extensor compartment of patients with De Quervain tenosynovitis undergoing a surgical treatment and correlate findings with human cadaveric wrists. Materials and Methods: From January 2013 to April 2014, 101 patients underwent tenolysis of the first tunnel extensor of the wrist, 82 women (82%) and 19 men (19%) with mean age of 55.4 years . Concomitantly, 65 cadaver wrists kept in formaldehyde were dissected, being 32 males (49%), 13 female (20%) and 20 without identification of the genus (31%). Results: Anatomical variations were observed in all operated patients. The presence of septation of the first tunnel was identified in 63 patients (62%). Supernumerary tendons of the long abductor of the thumb occurred in 87 patients (86,1%). Anatomical variations of the short extensor of the thumb occurred in eight patients (8%). In cadavers, 51 wrists (79%) showed no septation of the first tunnel and 31 (48%) found a single tendon of the long abductor of the thumb. All cadaveric wrists showed only one short extensor tendon of the thumb. The number of tunnels and long thumb abductor tendons were higher in operated patients when compared to corpses (p <0.01). No difference was observed in the amount of extensor tendons (p = 0.08) between patients and cadaveric wrists. Conclusion: Anatomical variations such as the presence of septation of the first extensor and supernumerary tendon of the long abductor of the thumb may be related to De Quervain tenosynovitis because all the patients operated were observed anatomical variations. Anatomical variations are usual in assintomatic population.